Protective Effects of Physical Exercise in Alzheimer's Disease and Parkinson's Disease: A Narrative Review - Paillard, Thierry; Rolland, Yves; de Souto Barreto, Philipe (Journal of clinical neurology (Seoul, Korea), 2015)
Alzheimer's disease (AD) and Parkinson's disease (PD) are devastating, frequent, and still incurable neurodegenerative diseases that manifest as cognitive and motor disorders. Epidemiological data support an inverse relationship between the amount of physical activity (PA) undertaken and the risk of developing these two diseases. Beyond this preventive role, exercise may also slow down their progression. Several mechanisms have been suggested for explaining the benefits of PA in the prevention of AD. Aerobic physical exercise (PE) activates the release of neurotrophic factors and promotes angiogenesis, thereby facilitating neurogenesis and synaptogenesis, which in turn improve memory and cognitive functions. Research has shown that the neuroprotective mechanisms induced by PE are linked to an increased production of superoxide dismutase, endothelial nitric oxide synthase, brain-derived neurotrophic factor, nerve growth factor, insulin-like growth factor, and vascular endothelial growth factor, and a reduction in the production of free radicals in brain areas such as the hippocampus, which is particularly involved in memory. Other mechanisms have also been reported in the prevention of PD. Exercise limits the alteration in dopaminergic neurons in the substantia nigra and contributes to optimal functioning of the basal ganglia involved in motor commands and control by adaptive mechanisms involving dopamine and glutamate neurotransmission. AD and PD are expansive throughout our ageing society, and so even a small impact of nonpharmacological interventions, such as PA and exercise, may have a major impact on public health.